2006
DOI: 10.1177/1043659605285410
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Graduating Nursing Students Regarding Life Experiences That Promote Culturally Competent Care

Abstract: This article describes a qualitative study that explored the perceptions of graduating students from a northeast baccalaureate nursing program regarding their life experiences with cultural diversity. Thirteen students were interviewed using an interview guide, and interviews were recorded on audiotape. Information obtained included participants' cultural heritage, life experiences before entering a nursing program, educational and clinical experiences in the nursing program, knowledge about cultural competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 9 publications
3
30
1
Order By: Relevance
“…This belief of the lack of relevance of cultural competency due to a desire for more didactic objective clinical learning and the perception that objective clinical content is more practical is consistent with previous research [21,26] . Reeves and Fogg [21] noted that factors that promoted cultural competency among nursing students were previous exposure to diverse cultures while growing up, and during Nursing school, and a desire to learn about other cultures. Maine is currently the Whitest state in the nation [67] , resulting in limited exposure of some of the state's residents to people of other cultural and racial backgrounds.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This belief of the lack of relevance of cultural competency due to a desire for more didactic objective clinical learning and the perception that objective clinical content is more practical is consistent with previous research [21,26] . Reeves and Fogg [21] noted that factors that promoted cultural competency among nursing students were previous exposure to diverse cultures while growing up, and during Nursing school, and a desire to learn about other cultures. Maine is currently the Whitest state in the nation [67] , resulting in limited exposure of some of the state's residents to people of other cultural and racial backgrounds.…”
Section: Discussionsupporting
confidence: 88%
“…However, the association between perceived self-competency and CCA scores was not present in the post-test, indicating that by the end of the course, low perceived competency was no longer a factor in CCA scores. The experience of conducting the Cultural Assessment Interview addressed several factors that have been shown to hinder students' perceptions of cultural competency including lack of experience with other cultures and lack of experience with cultural assessment tools [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blacks, Asians, American Indians, Alaska Natives, and Hispanics receive poorer quality care than Whites and have limited access to care when compared to Whites within the United States, according to the 2010 National Healthcare Quality Report and National Healthcare Disparities Report issued by the USDHHS Agency for Healthcare Research and Quality (AHRQ). Research by Reeves and Fogg (2006) found that only 50% of U.S. nursing graduates stated that they were comfortable providing care to individuals who were different from their own ethnic or cultural backgrounds.…”
Section: Introductionmentioning
confidence: 97%
“…Anna reflected on the impact of her experience: It is the responsibility of nurse educators to prepare nursing students for success as practicing nurses. Reeves and Fogg (2006) explored life experiences of nursing students that promoted culturally competent care in response to faculty differences about the inclusion of cultural content in the nursing curriculum. They conclude that nurse educators are ideally poised to provide guidance into the role of caring for a multicultural society.…”
Section: Immersion and The Future Of Nursing Educationmentioning
confidence: 99%